2019
DOI: 10.3390/ani9110968
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Reproductive Disorders, Parity, and Litter Size on Milk Yield of Serrana Goats

Abstract: Simple SummaryThis study aimed to evaluate the effects of reproductive disorders, parity, and litter size on a 150-day standardized milk yield of the Transmontano ecotype of the Serrana goat breed (a dual purpose breed) over a three decade period. The 150-day standardized milk yield was significantly influenced by all studied factors and their interactions. The milk yield reduction due to reproductive disorders was more intense in primiparous than multiparous goats, and in primiparous or multiparous goats of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 48 publications
1
15
0
Order By: Relevance
“…showed that the does with a calving rate at least twice had an average number of calving of 1.72 kids/doe, the highest value of 2.12 kids/doe, and the lowest value of 1.42 kids/doe and the medium category. The number of kids per calving from ILEG is higher than that of goats in Romania, with average kids per calving of 1.30 kids/doe (Pascal and Zaharia, 2016) and 1.43 kids/doe of Serrana goat (Margatho et al, 2019), 1.63 kids/doe of Begait goat (Abraham et al, 2018). It was almost the same as the average number of kids at German Improved Fawn goats with the kids per calving around1.70 kids/doe (Samardzija et al, 2013), and the ordinary calving of Saanen goats were 1.74 kids/doe (Kasap et al, 2013).…”
Section: Results and Discussion Prolific Data Of Ileg Doesmentioning
confidence: 99%
“…showed that the does with a calving rate at least twice had an average number of calving of 1.72 kids/doe, the highest value of 2.12 kids/doe, and the lowest value of 1.42 kids/doe and the medium category. The number of kids per calving from ILEG is higher than that of goats in Romania, with average kids per calving of 1.30 kids/doe (Pascal and Zaharia, 2016) and 1.43 kids/doe of Serrana goat (Margatho et al, 2019), 1.63 kids/doe of Begait goat (Abraham et al, 2018). It was almost the same as the average number of kids at German Improved Fawn goats with the kids per calving around1.70 kids/doe (Samardzija et al, 2013), and the ordinary calving of Saanen goats were 1.74 kids/doe (Kasap et al, 2013).…”
Section: Results and Discussion Prolific Data Of Ileg Doesmentioning
confidence: 99%
“…The gestation period can be influenced by season of the year, parity, age of the dam, sex and number of kids at birth (Solaiman 2010). Ribatejano and Transmontano are furthermore the most prolific ecotypes with 1.43 to 1.63 kids per kidding (ANCRAS 2020; Margatho et al 2019). Breed fertility is high varying between 90 and 95% and prolificity rates are between 170 and 180% (ANCRAS 2020), presenting frequently twin births (Pereira 2015).…”
Section: Serrana Breed Production Performancementioning
confidence: 99%
“…The number of sheep and goats farmers own was categorized as small (<7 sheep/ goats), medium (8-12 sheep/goats) and large (>12 sheep/goats) flock sizes. Parity number was categorized as nulliparous (zero parity), monoparous (parity one) and pluriparous (≥ two parities) (Margatho et al, 2019). Management systems were classified as extensive and semi-intensive based on the criteria adopted by Gizaw et al (2015).…”
Section: Study Design and Animalsmentioning
confidence: 99%
“…8) guidelines for body condition scoring and for all sheep and goats under the study their body condition grouped into three groups (poor, medium and good). Abortion was defined as loss of fetus or fetuses before 140 days of pregnancy (Margatho et al, 2019). The gestation stage of abortion was categorized as first trimester (<50 days), second trimester (51-100 days) and third trimester (101-154 days) (Bokko, 2011).…”
Section: Study Design and Animalsmentioning
confidence: 99%